Análise dos componentes de cobertura, de qualidade e da taxa de resolubilidade da internação hospitalar na Atenção em Saúde das macrorregiões do SUS: contribuições para delinear uma tipologia de rede assistencial. - Lenir Aparecida Chaves (2022)
The study is about the organization of Health Care Networks (RAS) at the Single Health System (SUS). Since the creation of the SUS, in 1988, regionalization has experienced different cicles, with descentralization prevailing in the period from 1988 to 2000 and, 2000 to the presente day, the construction of the Health Care Networks beggins, establishing a major challenge, due the the necessary inter-federative arrangements, between the diferente levels of care, for the conformation of governance in the care netwark. The objective was to point out the different configuration of RAS in Primary Care (AB) and hospital Care (AH), from coverage, quality and resolution characteristics in the SUS health macro-regions. This is a cross-sectional study, with data from the PMAQ-AB (2013-2014); the PNASS (2015-2016); e-Gestor AB System and DATASUS. Primarily, was built a performance score for the hospitals evaluated in the National Health Services Evaluation Program (PNASS 2015-2016). Then, the cluster statistical technique was used, which allows classifying elements into groups and identifying a “natural” structure of the observations based on a multivariate profile. The variables used were coverage and quality at AB-AH and the resolution rate of medium complexity hospital admission. The unit of analysis was the health macro-region. In the cluster analysis, the NbClust function was used to define the optimal number of groups. Average Score (EM) was obtained for each variable per group and a scale was also constructed for classifying the groups using the percentile (P). The Kruskal-Wallis and Nemenyi test was applied to compare the variables by region; calculated the quantity and percentage of macro-regions, municipalities and population for each group and summarized for Brazil by federated unit and region, observing how its population distribution occurs. Additionally, the description of the clusters compared the EM obtained in each variable with the classification scale constructed. Thus, the macro-regions were segmented according to groups with distinctive coverage, quality and solvability profiles to name a label capable of describing the nature of the aggregates and, thus, delineate a typology of care network. The results demonstrate that the optimal number of groups was: group 1 (High Coverage/AB and Medium/AH; Low Quality/AB-AH with High Resolvability); group 2 (High Coverage/AB and Low/AH; Low Quality/AB-AH with Medium Resolvability) and Group 3 (High Coverage/AB and Medium/AH; High Quality/AB-AH with High Resolvability). The analysis showed, in AB, high coverage for 100% of the Brazilian population, with (58.54%) accessing services of low quality and (41.15%) of high quality. In AH, coverage is low for (9.7%) of the population and medium for (90.29%), with (58.54%) accessing services of low quality and (41.15%) of high quality. Resolvability is high for (90.29%) of the population and medium for (9.7%). It was observed that a scenario of high coverage and low quality/AB prevails in Brazil; medium coverage and low quality/HA with high resolution in mediumcomplexity hospital admissions. However, for two-fifths of the population, a scenario of high coverage and quality/AB stands out; medium coverage and high quality/AH with high resolution. It is concluded that the interfederative relationship constitutes a major challenge in the institutional design of public policies. In the SUS, it materializes in the complexity of effecting a regional systemic integration, calling attention to the importance of the territorial dimension and the political-administrative role of the federated entities in the implementation of a universal, equitable and integral health system.